DEFINING OF THE SOCIO-PSYCHOLOGICAL READINESS PARAMETERS TO DIFFERENT FORMS OF LIFE ARRANGEMENT IN ORPHANS - Сафонова, Світлана Борисівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
In the article we analyzed the problem of determining the psychological readiness of orphans for moving in different forms of life arrangement. It was found that at the legislative level the procedure of preparation was not detailed, only the practical experience had some changes. It was established that during the preparation of orphans for different forms of life arrangement we should take into account such factors as past experience, age, personality, motivation and presence of relatives. Teenagers motivation for the moving into different forms of arrangement has a sense of freedom and understanding that adoptive parents will be the mentors for them. Primary school children have the desire of the family, which will love and take care of them.